Challenges of constructing legitimacy in peacebuilding : Afghanistan, Iraq, Sierra Leone, and East Timor - Higashi, Daisaku, 1969- (London ; New York : Routledge, 2015)
'The objective of this book is to develop an understanding of the mechanisms for constructing--or eroding--the legitimacy of newly created governments in post-conflict peacebuilding environments'--
1. Constructing or eroding legitimacy in peacebuilding -- 2. Compliance and noncompliance with disbanding illegal armed groups -- 3. Worsening security conditions and reconciliation efforts : insurgency noncompliance with the government -- 4. Conclusion.
Includes bibliographical references and index.
Mode of access : World Wide Web.
Keywords: Legitimacy of governments -- Developing countries; Peace-building -- Developing countries; International relations; Electronic books